Implementation Challenges of the 2030 Africa Agenda on Zero Hunger: Evaluating Progress Toward Sustainable Development Goal 2 - Darboe, Jalika; Nyeleker, Kerkulah P; Nurmandi, Achmad (INDONESIAN GOVERNANCE JOURNAL : KAJIAN POLITIK-PEMERINTAHAN, 2025)
Recently, reducing hunger has become a top priority on Africa’s development agenda. Despite efforts by governments and international donors, hunger continues to worsen across the continent. While much of the existing research has focused on the political and socio-economic drivers of hunger in Africa, few studies have explored the challenges faced when implementing policies aimed at addressing this issue, such as the 2030 Africa Agenda on Zero Hunger. This study aims to fill this gap by examining the integration, adaptability, and goal achievement of the policy using Richard M. Steers’ Effectiveness Theory as a framework. Qualitative data were collected through in-depth interviews, policy reports (2016–2024), peer-reviewed articles, and other relevant documents, then analysed with NVivo 12 Plus. The findings reveal barriers to integration caused by poor communication and limited consensus-building among stakeholders, and challenges in adaptation related to insufficient local contextualisation and capacity building. Concerning goal attainment, hunger has increased from 270.6 million to 295 million in 2024, food insecurity stands at 57.9%, and agricultural investments have decreased by 2.69%. This research contributes to the existing literature by illustrating how weak implementation can hinder policy goals, emphasising the need for more inclusive, context-sensitive, and well-coordinated strategies across Africa.